(untitled) (International Journal of Innovative Technologies in Economy, 2024)
This scientific article with the material "Fundamental and Technical Analysis on Stock Transactions" discusses the importance of fundamental and technical analysis in conducting transactions in the capital market. Stock trading is one of the investment alternatives in the capital market that is most widely used by investors because the profits are greater and the funds needed by investors to make investments are not that large when compared to bonds. The individual’s goal of trading stocks is to maximize welfare by maximizing the value of the company’s shares which will ultimately reflect the price of the shares whether it is good to buy or not.